2002
DOI: 10.1182/blood.v99.5.1692
|View full text |Cite
|
Sign up to set email alerts
|

A tyrosine703serine polymorphism of CD109 defines the Gov platelet alloantigens

Abstract: The biallelic platelet-specific Gov antigen system-implicated in refractoriness to platelet transfusion, neonatal alloimmune thrombocytopenia, and posttransfusion purpura-is carried by the glycosylphosphatidylinositol (GPI)-linked protein CD109. The recent identification of the human CD109 complementary DNA (cDNA) has allowed the molecular nature of the Gov alleles to be elucidated. By using reverse transcriptase-polymerase chain reaction (RT-PCR) to amplify CD109 cDNAs from 6 phenotypically homozygous Gov aa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 14 publications
1
97
0
Order By: Relevance
“…The conservation of other large amino acids blocks in the amino terminus is also much higher than in the block around the GCGEQ motif indicating that these amino acid 'blocks' may have an important functional or structural role. Evolutionarily speaking, the change which resulted in the Gov a/b alleles is probably due to the ''Gov b'' serine being replaced by a tyrosine in ''Gov a'' Schuh et al, 2002), because the murine sequence contains a serine, not a tyrosine, at a similar position.…”
Section: Discussionmentioning
confidence: 98%
“…The conservation of other large amino acids blocks in the amino terminus is also much higher than in the block around the GCGEQ motif indicating that these amino acid 'blocks' may have an important functional or structural role. Evolutionarily speaking, the change which resulted in the Gov a/b alleles is probably due to the ''Gov b'' serine being replaced by a tyrosine in ''Gov a'' Schuh et al, 2002), because the murine sequence contains a serine, not a tyrosine, at a similar position.…”
Section: Discussionmentioning
confidence: 98%
“…K02404.) nucleotide polymorphism of the cDNA reported here (see accompanying article by Schuh et al, 53 page 1692). Nevertheless, the presence of multiple CD109 transcripts by Northern blot analysis and the presence of an additional CD109-related peptide that could not be accounted for by our cDNA raise the possibility that additional CD109 cDNA variants may exist.…”
Section: Discussionmentioning
confidence: 99%
“…Most HPAs are based on single-nucleotide polymorphisms resulting in amino acid substitutions localized on the main platelet receptors: integrin αIIbβ3 (GPIIb/IIIa, CD41/CD61: the fibrinogen receptor), the GPIb-IX-V complex (CD42, von Willebrand factor receptor), and the GPIa/IIa complex (α2β1, CD29, the collagen receptor) 9,10. HPA-15 is the only exception; this biallelic system is carried by the platelet membrane protein CD109,11 which is a part of the transforming growth factor-β receptor system 12. For a more comprehensive presentation of platelet membrane glycoproteins, the recent review by Zdravic et al13 is suggested.…”
Section: Pathogenesismentioning
confidence: 99%